Lateralized Movements during the Mating Behavior, Which Are Associated with Sex and Sexual Experience, Increase the Mating Success in Alphitobius diaperinus (Coleoptera: Tenebrionidae) - Calla-Quispe, E.; Irigoin, E.; Mansurova, M.; Martel, C.; Ibáñez, A.J. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In the present study, we explored the effects of displacement directionality in mating behavior (i.e., lateralized and non-lateralized movements) on mating success (i.e., copulation occurs) and efficiency (i.e., time length at which copulation is achieved), and its association with sex and sexual experience in A. diaperinus. To do so, we carried out mating experiments and recorded the behavior of the mating pair during the whole mating sequence (i.e., precopulatory and copulatory phases). During the precopulatory phase, independently of sex and sexual experience, all beetles performed non-lateralized (i.e., backside or frontside) approaches; however, only sexually experienced beetles showed lateralized approaches (i.e., right-side and left-side). Notably, experienced males exhibited greater mating success than virgin males. After the approach, both virgin and experienced males displayed lateralized and non-lateralized mounts on the females with distinct mating success. Regardless of their sexual experience, 100% of successful mating attempts were achieved when males mounted from the females’ right side. Furthermore, the development of lateralized approaches and mounts reduces the time of mating sequence span compared with non-lateralized behaviors. We highlight the importance of lateralization in mating behavior and sexual experience to achieve higher mating success, addressing a potential learning ability of beetles based on experience.
Keywords: Mating; Biology; Zoology; Lateralization of brain function; Sexual behavior; Ecology; Developmental psychology; Psychology; Neuroscience; https://purl.org/pe-repo/ocde/ford#1.06.11